Evaluating the Effect of Managerial Effectiveness on Perceived Organizational Performance: Evidence from Nepalese Commercial Banks - Maharjan, Purna Narayan (PYC Nepal Journal of Management, 2024)
Managerial effectiveness is crucial in improving the banking sector’s operational efficiency, customer experience, and service quality. This research investigates how managerial effectiveness affects Nepalese commercial banks’ perceived performance. A causal research design was utilized to evaluate the impact of managerial effectiveness on perceived organizational performance. By adopting a convenient sampling method, the study surveyed 425 branch managers and deputy managers from commercial banks in Nepal. Inferential statistical techniques, including structural equation modeling (SEM) through path analysis, were utilized to examine the proposed causal relationship. The findings emphasize the strong effect of managerial effectiveness on perceived organizational performance, reinforcing its significance in enhancing the overall performance of Nepalese commercial banks. These insights contribute to the academic literature on banking management while offering valuable recommendations for bank managers and policymakers, guiding them toward performance improvement through effective leadership. Additionally, the study outlines potential directions for future research, encouraging further examination of managerial effectiveness across different sectors.